Does skeletal muscle have an 'epi'‐memory? The role of epigenetics in nutritional programming, metabolic disease, aging and exercise. Issue 4 (22nd April 2016) - Sharples, Adam P.; Stewart, Claire E.; Seaborne, Robert A.
Summary: Skeletal muscle mass, quality and adaptability are fundamental in promoting muscle performance, maintaining metabolic function and supporting longevity and healthspan. Skeletal muscle is programmable and can 'remember' early‐life metabolic stimuli affecting its function in adult life. In this review, the authors pose the question as to whether skeletal muscle has an 'epi'‐memory? Following an initial encounter with an environmental stimulus, we discuss the underlying molecular and epigenetic mechanisms enabling skeletal muscle to adapt, should it re‐encounter the stimulus in later life. We also define skeletal muscle memory and outline the scientific literature contributing to this field. Furthermore, we review the evidence for early‐life nutrient stress and low birth weight in animals and human cohort studies, respectively, and discuss the underlying molecular mechanisms culminating in skeletal muscle dysfunction, metabolic disease and loss of skeletal muscle mass across the lifespan. We also summarize and discuss studies that isolate muscle stem cells from different environmental niches in vivo (physically active, diabetic, cachectic, aged) and how they reportedly remember this environment once isolated in vitro . Finally, we will outline the molecular and epigenetic mechanisms underlying skeletal muscle memory and review the epigenetic regulation of exercise‐induced skeletal muscle adaptation, highlighting exercise interventions as suitable models to investigate skeletal muscle memory in humans. We believe that understanding the 'epi'‐memory of skeletal muscle will enable the next generation of targeted therapies to promote muscle growth and reduce muscle loss to enable healthy aging.